(untitled) (Asean Journal of Engineering Education, 2025)
This research explores the impact of scaffolding in Project-Based Learning (PjBL) on the development of students’ metacognitive skills. Metacognitive skills are crucial in engineering courses as they enable students to navigate complex tasks by self-monitoring and adjusting strategies. The research designed a multi-layered scaffolding approach incorporating structured tasks, staged feedback, reflective prompts, and group discussions to support learning and reflection in a "Cultural and Technological Food Cart Design Challenge." Based on Vygotsky’s Zone of Proximal Development (ZPD) and constructivist theories, the scaffolding provided guidance at various learning stages, progressively enhancing students’ understanding, monitoring, and information management skills. Using a mixed-method approach, quantitative data were collected through the Metacognitive Awareness Inventory (MAI) to track metacognitive progress, while qualitative data from daily reflection logs captured students’ experiences. Results showed significant improvements in metacognitive skills in comprehension monitoring and information management (p < 0.05), though limited project duration restricted the development of planning and self-evaluation skills. The research offers optimization insights for scaffolding in PjBL, particularly highlighting the positive effects of scaffolding on emotional regulation and self-motivation in cross-cultural projects, providing a reference for future pedagogical practices in complex tasks.